Segregation of late outgrowth endothelial cells into functional endothelial CD34− and progenitor-like CD34+ cell populations - Ferreras, Cristina; Urban, Katharina (Angiogenesis, 2015)
Late outgrowth endothelial cells (OECs) that originate from peripheral blood mononuclear cells ex vivo have phenotypic and functional properties of mature endothelial cells. Given the potential therapeutic applications of OECs, understanding their biology is crucial. We have identified two distinct OEC populations based on differential expression of the cell surface marker CD34. OEC colonies lacked CD34 expression (CD34−), expressed CD34 in the majority of cells (CD34+), or showed a mixed expression pattern within a colony (CD34+/−). CD34+ and CD34− OECs were negative for hematopoietic cell marker CD45 and expressed the endothelial cell surface markers CD31, CD146, CD105, and VEGFR-2. Functionally CD34− and CD34+ OECs exhibited strikingly distinct behaviors. CD34− OECs, unlike CD34+ OECs, were capable of sprouting, formed tubes, and responded to angiogenic growth factors in vitro. In vivo, CD34− OECs formed endothelial tubes, while CD34+ OECs, despite being unable to form tubes, promoted infiltration of murine vasculature. Global gene expression profiling in CD34− and CD34+ OECs identified functional importance of the MMP-1/PAR-1 pathway in CD34− OECs. MMP-1 stimulated the expression of VEGFR-2, neuropilin-1, neuropilin-2, and CXCR4 and activated ERK1/2, whereas down-regulation of PAR-1 in CD34− OECs resulted in impaired angiogenic responses in vitro and reduced VEGFR-2 levels. In contrast, the CD34+ OEC colonies expressed high levels of the progenitor cell marker ALDH, which was absent in CD34− OECs. In summary, we show that OECs can be classified into functionally mature endothelial cells (CD34− OECs) that depend on the MMP-1/PAR-1 pathway and progenitor-like angiogenesis-promoting cells (CD34+ OECs).